The Implementation Of Curriculum 2013 In Teaching English At Smpn 8 Padang - Widya Juli Astria (Fakultas Sastra Universitas Ekasakti, 2017)
This research was aimed to find out the implementation of Curriculum 2013 in term of preparation, teaching learning process and assessment. The location of the research was at SMPN 8 Padang. The research used descriptive method. The data were taken through documentation, observation and field notes. The documentation of this research was the lesson plans designed by the teachers. Then, the researcher did observation to find out the process and assessment in the classroom. The result of this research showed that there was 88.21% of the lesson plans had been designed by the teachers based on the requirements of Curriculum 2013. But, in the teaching and learning process there were only 65% of aspects in the 2013 Curriculum have been implemented in teaching learning process. From the finding, it showed that 55% of activities in observing, questioning, associating steps had been done by the teachers. Meanwhile, there were 65% of activities in experimenting steps had been done by teachers. Then, there were 75% of activities in communicating step had been done well by the teachers. It indicated that the teachers still got problems in implementing observing questioning, and associating steps. Then, the teachers tended to use observation, project, portfolio, and oral test to assess students’ competences. Based on the findings above, it is shown that the aspects of Curriculum 2013 have not been implemented by all the teachers. Therefore, the English teachers of SMPN 8 Padang should learn more about how to implement Curriculum 2013 in teaching English. It is suggested to the head master to conduct more training for all English teachers on the Curriculum 2013 implementation. For next researcher, it is suggested to research the implementation of Curriculum 2013 with more samples to get further information..